Microwave transmittance of a high-Tc superconductor film in a magnetic field - Pishko, V. V. Eremenko V. A. Novosad V. V.; Falco, C.; Rashkovan, V. M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1999)
The results of microwave transmittance measurements of crystalline high-Tc YBaCuO film under the influence of an external magnetic field are presented. Generally, in high-Tc superconductors dissipation mechanisms different from those in conventional superconductors may take place as well as transport current, Josephson-junction and anisotropy resistance-connected processes. Measurements of transmittance induced by the magnetic field demonstrate the dominance of flux flow dissipation mechanism and nonlinear transmittance dependence when approaching Tc. This makes possible to detect and characterize all the mechanisms mentioned above.